MANAGEMENT OF SOFTWARE PRODUCT QUALITY OF IT PROJECTS IN CRISIS CONDITIONS - Stankovska I. М.; Smaga, L. R. (The actual problems of regional economy development, 2024)
The topic of the article is "Management of software product quality of IT projects in crisis conditions" The purpose of the study is to justify the need to improve quality management in crisis conditions, to determine the quality criteria of software products of IT projects, and to provide recommendations for improving quality management. In order to achieve the goal, methods of analysis (qualitative and quantitative) synthesis, interviewing, theoretical generalization, comparison, and modeling were used. The work examines the impact of the crisis (the COVID-19 pandemic and the full-scale invasion of Russia in 2022) on the work of IT organizations. It was established that clients need confidence in professional cooperation with mature organizations, and IT organizations need readiness for all possible options for the development of events in the state, which led to the need to pay attention to the quality management of software products and IT projects. The scientific novelty consists in determining the quality management metrics of the software product of the IT project; carrying out a comparative assessment of the application and measurement of the main quality management metrics in the pre-war years 2021 and 2023. The established criteria for assessing the quality of software products of IT projects have gained practical significance for proactive quality management, namely: the forecast of closing all backlog defects; effectiveness of defect identification; effectiveness of defect correction; the duration of the correction of defects of the first priority; the stage of achieving an intermediate goal; the level of fulfillment of obligations for the development iteration; the level of coverage by automatic tests; unit test coverage level. According to the research results, IT organizations are offered: - apply tools for monitoring and analyzing the level of quality in real time; - in quality management, evaluate both functional and non-functional aspects, such as performance, security and usability; - check each process of creating an IT product and implementing an IT project for efficiency and effectiveness.